THE EFFECT OF 3P METHOD USING INSTAGRAM VIDEO @5.MIN.CRAFTS ON GRADE VII STUDENTS PROCEDURAL WRITING SKILLS - Damayanti, Rahmah; Nurita Bayu Kusmayati; Reni Nur Eriyani (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This research aims to determine the effect of the Presentation, Practice, Production (3P) method assisted by the video media of the Instagram account @5.min.crafts on the ability to write procedural texts conducted on seventh-grade students at SMP Negeri 44 Jakarta. This study employs an experimental method with a pretest-posttest control group design. The sample in this study is class VII-G as the control class and class VII-H as the experimental class, selected using the Simple Random Sampling Technique. The results show a significant improvement in the experimental class, with the average post-test scores increasing from 48 to 85. Meanwhile, the control class increased from 45 to 63. Hypothesis testing using SPSS 25.0 shows a significance value (2-tailed) of 0.000 < 0.05, indicating a significant difference between the two classes. Thus, the 3P method supported by the Instagram video media @5.min.crafts has been proven to have a positive effect on the skills of writing procedural texts and can be an alternative to other language learning strategies.